i-Saraf – a web-based multimedia platform for learning Arabic morphology - Md. Noor, Mohamad Lukman Al Hakim; Sahrir, Muhammad Sabri; Abdul Aziz, Nur Farhana; Abdul Ghani, Muhamad Zamri (Centre for Teaching and Learning (CTL) and International Islamic University Malaysia (IIUM), 2018)
Saraf or Morphology is one of the branches of knowledge in Arabic Linguistic. Towards Technology 4.0 or known as Fourth Industrial Revolutions, the Internet of Things, the researcher believes that, learning Arabic morphology through the design of a computer assisted program by using multimedia via the World Wide Web would greatly help student in learning Arabic Morphology. Knowing that there are many students from Arabic language especially non-native speakers faced difficulties in learning Arab morphology, including the large number of morphological terms that lead to student psychological disorder, distraction of mind, and it becomes worst if they are presented with the views of scholar’s different views which lead them to avoid morphology subject due to its complexity and difficulty material based on learners’ perception. This study adopted two methodologies of descriptive and analytical. After collected information about the difficulties in learning Arabic morphology, theories of learning Arabic language via the World Wide Web, the researcher designed a computer assisted program by using multimedia via the URL of http://efolio.iium.edu.my/courses/ sorof / index.html through the website of Blendspace. It was developed in the light of instructional design model of ADDIE based on the views of the respondents and their suggestions and needs. The researcher found that this multimedia learning programme is highly accepted by the respondents, as it leads to a productive and successful process of learning Arabic morphology.